Exergame: Exercise With Matching Memory Game On Cognitive Function And Physical Fitness Of The Elderly - Dwi Pratiwi, Gilang; Hadiyani, Wini; Lucya, Vita; Gumelar, Yuda (Poltekkes Kemenkes Surakarta, 2024)
Background: Cognitive decline and physical deterioration are common issues among the elderly, significantly impacting their quality of life. The unanticipated cognitive impairments will result in dementia. Effective approaches to simultaneously improving both aspects remain to be further developed and evaluated. Exercise with a matching memory game overcomes the issues. This study aimed to examine the effectiveness of an exergame, combining memory-stimulating games and physical exercise in improving cognitive function and physical fitness among the elderly. Methods: The study was a quick experiment with two groups in a pre-post test design. A number of 119 participants were recruited using purposive sampling and randomly divided into the experimental group (n=60) or the control group (n=59). Cognitive function was assessed using the Mini-Mental State Examination (MMSE), while physical fitness was measured with the 2-minute step test score. Results: The data was analyzed using a paired t-test, which revealed a significant improvement in MMSE and 2-minute scores in the experimental group before and after the intervention (p < 0.05). Additionally, the independent t-test analysis demonstrated a significant difference between the experimental and control groups in both cognitive and physical fitness measures after the intervention (p < 0.05). Conclusion: Implementing exercise has a significant positive influence on cognitive function and physical fitness among the elderly. Incorporating an exergame into community health programs for the elderly could provide substantial benefits to their overall well-being.